ANALISIS PENERAPAN MODEL PICTURE AND PICTURE DALAM MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPA KELAS V SDN MASIMBU KECAMATAN BARAS KABUPATEN PASANGKAYU - Sri Wahyuni; Kasmiati; Mirnawati (Koordinat Jurnal MIPA, 2022)
The problem raised in this study is how to analyze the application of the Picture and Picture model in increasing the active learning of students in science subjects in class V at SDN Masimbu. This research is a qualitative research with descriptive type. The research location is at SDN Masimbu, the data sources are obtained from primary data and secondary data. The data collection used is observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion drawing/data verification. The results showed that SDN Masimbu has implemented several learning models to help the continuity of learning, one of which is the Picture and Picture learning model. The application of the Picture and Picture model is carried out according to indicators and learning steps by presenting learning materials using pictures given to groups of students to conduct discussions and present the results of their discussions. The results of the analysis show that the application of the Picture and Picture model with several steps of the learning model used has been carried out well. The learning activity of students is increasing and students are becoming more active in the learning process, although with some obstacles experienced by the teacher in the process of implementing it, the teacher can overcome these obstacles well.